2D EPID dose calibration for pretreatment quality control of conformal and IMRT fields: A simple and fast convolution approach. Issue 1 (January 2016) - Camilleri, Jérémy; Mazurier, Jocelyne; Franck, Denis; Dudouet, Philippe; Latorzeff, Igor; Franceries, Xavier
Highlights: An original 2D algorithm that converts the signal of an EPID to absorbed dose in water was created. We demonstrated that our method is usable both for 3DCRT and IMRT techniques. The proposed algorithm is really fast and easy to implement in clinical routine compared to other studies. Abstract: Purpose: This work presents an original algorithm that converts the signal of an electronic portal imaging device (EPID) into absorbed dose in water at the depth of maximum. Methods: The model includes a first image pre-processing step that accounts for the non-uniformity of the detector response but also for the perturbation of the signal due to backscatter radiation. Secondly, the image is converted into absorbed dose to water through a linear conversion function associated with a dose redistribution kernel. These two computation parameters were modelled by correlating the on-axis EPID signal with absorbed dose measurements obtained on square fields by using an ionization chamber placed in water at the depth of maximum dose. The accuracy of the algorithm was assessed by comparing the dose determined from the EPID signal with the dose derived by the treatment planning system (TPS) using the ϒ-index. These comparisons were performed on 8 conformal radiotherapy treatment fields (3DCRT) and 18 modulated fields (IMRT). Results: For a dose difference and a distance-to-agreement set to 3% of the maximum dose and 2 mm respectively, the mean percentage of points with a ϒ-value less than or equal to 1 was 99.8% ± 0.1% for 3DCRT fields and 96.8% ± 2.7% for IMRT fields. Moreover, the mean gamma values were always less than 0.5 whatever the treatment technique. Conclusion: These results confirm that our algorithm is an accurate and suitable tool for clinical use in a context of IMRT quality assurance programmes.